2018
DOI: 10.1111/chd.12637
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic velocity half time is associated with aortic coarctation gradient at catheterization independent of echocardiographic and clinical blood pressure gradients

Abstract: Objective: The most accurate non-invasive parameter to predict whether a patient with aortic coarctation will meet interventional criteria at catheterization remains elusive. We aim to determine the best independent echocardiographic predictors of a coarctation peak-to-peak pressure gradient ≥ 20 mmHg at catheterization, the accepted threshold for intervention. Design: Retrospective query of our catheterization database from 1/2007 – 7/2016 for the diagnostic code of aortic coarctation was performed. Multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The patient’s ECG was suggestive of left ventricular hypertrophy, a consequence of the chronically increased afterload and systemic arterial hypertension. Transthoracic echocardiography revealed typical antegrade diastolic flow in the descending thoracic aorta with a “saw tooth” pattern ( 2 , 26 ). In adults, the location opposite the ductus/ligamentum arteriosus is the most commonly encountered location of CoA ( 5 , 6 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s ECG was suggestive of left ventricular hypertrophy, a consequence of the chronically increased afterload and systemic arterial hypertension. Transthoracic echocardiography revealed typical antegrade diastolic flow in the descending thoracic aorta with a “saw tooth” pattern ( 2 , 26 ). In adults, the location opposite the ductus/ligamentum arteriosus is the most commonly encountered location of CoA ( 5 , 6 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 In practice, the pressure gradient across the isthmus as measured by TTE is commonly considered an indication for re-CoA intervention. 18 The cutoff peak gradient across the stenotic area indicative of arch reintervention has been reported to be 20 to 30 mm Hg. 5,7,9 However, because of the poor correlation between the gradient determined by echocardiography and the peak-to-peak gradient at catheterization, the definition of re-CoA varies among centers and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,9 However, because of the poor correlation between the gradient determined by echocardiography and the peak-to-peak gradient at catheterization, the definition of re-CoA varies among centers and clinicians. 18 In our clinical practice, re-CoA is usually diagnosed when there is a peak gradient !35 mm Hg across the isthmus on TTE. For some specific re-CoA morphologies, the gradient may be overestimated or underestimated on TTE.…”
Section: Discussionmentioning
confidence: 99%
“…Most peak Doppler obtained gradients showed moderate correlation (r = 0.503-0.617, p<0.001) with gradients obtained at catheterization. It was found that noninvasive four extremity blood pressure gradients correlated significantly only if peak gradient was ≥ 20 mmHg [15]. Wisotzkey with 34 (57%) native coarctation and 26 (43%) aortic re-coarctation.…”
Section: Literature Reviewmentioning
confidence: 96%
“…According to Christopher et al [15] retrospective study with 68 patients of whom 84% underwent intervention during catheterization. Most peak Doppler obtained gradients showed moderate correlation (r = 0.503-0.617, p<0.001) with gradients obtained at catheterization.…”
Section: Literature Reviewmentioning
confidence: 99%